Beyond Ideal Theory: Foundations for a Critical Rawlsian Theory of Climate Justice. Issue 4 (2nd October 2021) - Clements, Paul; Formosa, Paul
ABSTRACT: Rawls's contractualist approach to justice is well known for its adoption of ideal theory. This approach starts by setting out the political goal or ideal and leaves it to non-ideal or partial compliance theory to map out how to get there. However, Rawls's use of ideal theory has been criticized by Sen from the right and by Mouffe from the left. We critically address these concerns in the context of developing a Rawlsian approach to climate justice. While the importance of non-ideal theory for climate justice is increasingly being understood, its strategic and institutional importance for a Rawlsian approach needs further elaboration. We focus on the role of the Kantian conception of the reasonable and rational powers of persons in Rawls's work and show how this helps us to develop a partial compliance theory that focuses on the importance of institutions and strategic political action for achieving climate justice.